2016
DOI: 10.1097/bsd.0b013e3182aa4ce1
|View full text |Cite
|
Sign up to set email alerts
|

A Genetic Test Predicts Providence Brace Success for Adolescent Idiopathic Scoliosis When Failure Is Defined as Progression to >45 Degrees

Abstract: We demonstrate that a genetic test correlates with bracing outcome. It may be appropriate for future bracing studies to include analysis of genetic predisposition to limit potential confounding.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 3 publications
1
15
0
Order By: Relevance
“…Several previous studies have reported that different characteristics can be used for the prediction of severe spine deformity, such as clinical [ 27 ], radiographic [ 28 ], physiologic [ 29 ], biochemical [ 30 ], genetic [ 31 ], and combinatorial parameters [ 32 ]. Tan et al [ 21 ] examined 186 AIS patients and noted that curve magnitude more than 30 degrees at first session was the most important predictive factor for curve progression.…”
Section: Discussionmentioning
confidence: 99%
“…Several previous studies have reported that different characteristics can be used for the prediction of severe spine deformity, such as clinical [ 27 ], radiographic [ 28 ], physiologic [ 29 ], biochemical [ 30 ], genetic [ 31 ], and combinatorial parameters [ 32 ]. Tan et al [ 21 ] examined 186 AIS patients and noted that curve magnitude more than 30 degrees at first session was the most important predictive factor for curve progression.…”
Section: Discussionmentioning
confidence: 99%
“…According to the research performed, a total of 40 papers [ 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 43 , 44 , 45 , 46 , 47 , 48 , 49 , 50 , 51 , 52 , 53 , 54 , 55 ] met the inclusion criteria and were considered for review. Of these studies, twenty-one [ 18 , 19 , 21 , 24 , 31 , 33 , 35 , 36 , 37 , 38 , 39 , 40 , 41 , 42 , 44 , 45 ,…”
Section: Resultsmentioning
confidence: 99%
“…The test is no longer available after ScoliScore failed in 2 independent analyses conducted in Caucasian and Asian populations [ 28 , 29 ]. In 2016, Bohl et al demonstrated that the ScoliScore genetic test correlates with bracing outcome and may be appropriate for future bracing studies [ 30 ].…”
Section: Discussionmentioning
confidence: 99%